The Effect of Profitability on Social Responsibility (CSR) in Indonesia: Environmental Performance as a Moderator - Khusnik Hudzafidah; Umi Rahma Dhany; Ahmad Iskandar Rahmansyah (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
This article analyzes the effect of return on assets (ROA) and return on equity (ROE) on social responsibility disclosure with environmental performance as a moderating variable in manufacturing sector companies listed on the Indonesia Stock Exchange (IDX). The type of research used is quantitative by using smart PLS as statistical analysis. The sample in this study were issuers in the food and beverage sub-sector for the 2016-2020 period with a total of 11 companies using a purposive sampling method. The results of the study prove that there is a positive relationship between ROA and CSR disclosure, while return on equity has no significant effect on CSR disclosure. The environmental performance variable as a whole does not moderate CSR disclosure but has a positive effect on the dependent variable